Structural and mechanical modifications of GaN thin films by swift heavy ion irradiation. (January 2022) - Eve, Sophie; Ribet, Alexis; Mattei, Jean-Gabriel; Grygiel, Clara; Hug, Eric; Monnet, Isabelle
Abstract: The structural modifications and the evolution of mechanical behavior of gallium nitride (GaN) thin films irradiated by 92 MeV 129 Xe 23+ at different fluences have been investigated. The modifications induced by irradiation in GaN have been studied using a combination of high resolution X-ray diffraction and Transmission Electron Microscopy observations coupled to nanoindentation. The crystalline lattice of the GaN is modified by irradiation, with an extension of the lattice along the c -direction parallel to the ion path, leading to the development of residual stresses. Correlated to the crystallographic disorder, modification of the deformation mechanisms of the material is observed: damaged areas (highly disordered zones near the surface and black dots deeper in the bulk) hinder the dislocation motion, such as after irradiation, dislocation slip occurs only along the basal plane, and no more prismatic or pyramidal slip is observed. This results in increasing the dislocation loop density, with a subsequent increase in hardness of the GaN film. At higher fluence, the overlapping of the latent tracks created by swift heavy ions results in a significant decrease in the mechanical characteristics of the thin film, and an amorphous-like material behavior. Highlights: Irradiation of GaN leads to a high crystalline disorder and a lattice extension. The crystalline lattice deformation causes the development of residual stresses. These structural modifications due to irradiation hinder the dislocations slip. The mechanical behavior of the irradiated GaN is evaluated by nanoindentation. The plasticity of the irradiated GaN is reduced and its hardness increases.